Normalization of global longitudinal strain after 20 squats in elite athletes. (4th February 2022) - Bruin De- Bon, H; Verwijs, SM; Hattum Van, JC; Blomjous, AGA; Planken, RN; Boekholdt, SM; Groenink, M; Hoogenband Van Den, CR; Moen, MH; Wilde, AAM; Pinto, YM; Bouma, BJ; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background/Introduction: Transthoracic echocardiography (TTE) is often the first diagnostic imaging modality of choice in athlete care to differentiate between physiological adaptation to sports and pathology. Left ventricular (LV) global longitudinal strain (GLS) has been suggested as a tool to detect early signs of myocardial diseases in athletes. However, low rates of myocardial deformation can also be associated with cardiac adaptation to sports. We hypothesized that observing decreased cardiac deformation in elite athletes may be a sign of an outspoken relaxed cardiac state, rather than pathology. Therefore, we investigated whether a short exercise bout can normalize strain values in elite athletes with abnormal resting GLS. Methods: We prospectively enrolled elite athletes who participated in the ELITE (Evaluation of Lifetime Participation in Intensive Top-level Sports and Exercise) cohort. In short, ELITE is a prospective athlete cohort, which collects medical history, ECG, TTE and cardiac magnetic resonance (CMR) data in elite athletes (Olympic/Paralympic level or comparable). For this analysis, we analysed TTEs of asymptomatic athletes without cardiovascular disease and with a structurally normal heart on CMR. TTE (Vivid, GE) was performed in each athlete according to guidelines at rest. After a short exercise bout, consisting of 20 squats, additional GLS, LV ejection fraction (EF), and LV stroke volume (SV) measurements were assessed when heart-rate (HR) was comparable to HR during pre-exercise measurements. TTE data was assessed using EchoPAC (GE). GLS delta (pre- to post-exercise) for each athlete was calculated were plotted, using R. GLS ≥ -16% was considered decreased and -16% ≥ GLS > -18% borderline. Results: Our population comprised 73 athletes (26% women), mean age (±SD) of 25.6 ± 6.5 years, BSA of 2 ± 0.2m2, and athletic disciplines road cycling (n = 28), soccer (n = 12), hockey (n = 8), swimming (n = 5), tennis (n = 5) and 8 miscellaneous sports (n = 15). Mean pre- and post-exercise GLS were -18.2 ± 2.1% vs -20.5 ± 2.0% (P < 0.001; Figure 1), EF 57 ± 4% vs 59 ± 6% (P = 0.006; Figure 1), SV 89 ± 20ml vs 99 ± 24ml (P = 0.008), and HR 56 ± 12bpm vs 56 ± 13bpm (P = 0.875). We observed an increase of myocardial deformation after a short bout of exercise: mean GLS delta of -2.3 ± 1.9%. Finally, we found a decreased strain in 14 athletes (19%), in which pre- and post-exercise GLS were -15.1 ± 0.8% and -18.6 ± 2.3%, P= <0.001, Figure 1). Only 1 athlete (1%, no other signs of cardiac pathology: MRI, biomarkers, complaints) had post-exercise decreased GLS. We found 9 athletes with a deteriorated cardiac deformation (delta GLS ≤ 0%), pre- and post-exercise GLS were -20.4 ± 1.4% and -19.9 ± 1.5% (maximal GLS post-exercise was -17.7%, Figure 1). Conclusion: GLS normalizes in 99% of healthy (elite) athletes. In athletes with decreased GLS at rest, performing a short exercise bout is a pragmatic method to separate decreased GLS due to pathology from sport adaptation